2020
DOI: 10.3389/fnbeh.2020.00114
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Ethanol Exposure Increases Ethanol Consumption Following Traumatic Stress Exposure in Mice

Abstract: Piggott et al. Behavioral Outcomes in PTSD-AUD Model mSPS and CIE are more vulnerable to ethanol withdrawal effects, and those exposed to mSPS have increased impulsivity, while CIE exposure increases anhedonia. Future studies to examine the relationship between behavioral outcomes and the molecular mechanisms in the brain after PTSD-AUD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This hyperlocomotion was accompanied by hyperactivity as evidenced by increased average speed in center of the open-field apparatus ( Figure 2D , p = 0.0008, t -test), total average speed ( Figure 2E , p < 0.0001, t -test) in the OF apparatus, and reduced latency to feed in the NSF, compared to water controls ( Figure 2F , p = 0.0005, t -test). Combined with hyperactivity, this lack of novelty-induced feeding inhibition could be interpreted as a reduction of impulse control to anxiogenic environment and further suggests that chronic sucrose consumption produces both hyperactivity and impulsivity ( Bevilacqua et al, 2010 ; Angoa-Pérez et al, 2014 ; Piggott et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hyperlocomotion was accompanied by hyperactivity as evidenced by increased average speed in center of the open-field apparatus ( Figure 2D , p = 0.0008, t -test), total average speed ( Figure 2E , p < 0.0001, t -test) in the OF apparatus, and reduced latency to feed in the NSF, compared to water controls ( Figure 2F , p = 0.0005, t -test). Combined with hyperactivity, this lack of novelty-induced feeding inhibition could be interpreted as a reduction of impulse control to anxiogenic environment and further suggests that chronic sucrose consumption produces both hyperactivity and impulsivity ( Bevilacqua et al, 2010 ; Angoa-Pérez et al, 2014 ; Piggott et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, long-term sucrose consumption reduced impulse control in the novelty-suppressed feeding, and this was not observed when sucrose access was restricted. Although novelty-suppressed feeding test is primarily to assess anxiety-like behaviors, studies have shown that a reduced latency to feed could be correlated with augmented food seeking and increased meal size ( Biddinger et al, 2020 ), increased hunger and reduced-feeding control after fasting ( Burghardt et al, 2016 ), and together with hyperlocomotion, increased motor impulsivity ( Bevilacqua et al, 2010 ; Angoa-Pérez et al, 2014 ; Piggott et al, 2020 ). This suggests that the reduced latency to feed we observed after long-term sucrose intake could be the result of impulsivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some work has exposed animals to EtOH prior to PTSD‐like stressors, these experiments assess changes in EtOH drinking following stress and do not examine EtOH‐induced changes in PTSD‐like behavior itself. For example, previous exposure to EtOH increases EtOH preference and consumption following exposure to PTSD‐like stressors (Piggott et al, 2020). Likewise, Zoladz et al (2018) confirmed that PTSD‐like stress increases EtOH intake in EtOH‐experienced animals, but also demonstrated that stress leads to decreased EtOH intake in EtOH‐naïve animals.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that traumatic stress combined with acute alcohol administration decreased CB1R levels in the mouse anterior STR compared to control groups [ 20 ]. Our previous reports have also shown that traumatic stress combined with chronic intermittent ethanol vapor exposure and withdrawal uniquely increased ethanol consumption compared to the control group (non-stress, air exposure) in mice [ 57 ]. However, no animal studies have been reported to examine the effects of traumatic stress combined with chronic ethanol exposure on the brain levels of the endocannabinoid ligands (AEA and 2-AG), their synthetic enzymes (NAPE-PLD and α-DAGL), their degradatory-hydrolytic enzymes (FAAH and MAG-L), and CB1R.…”
Section: Introductionmentioning
confidence: 99%